Performance of full sibs and their open-pollinated progenies in two varieties of maize - Yap, Thoo Chai; Hee, Yang Chiow (Faculty of Agriculture, University of Malaya, 1974)
Two experiments were conducted to evaluate whether the yielding ability of maize can be improved by bulking superior full sibs and/or their open-pollinated progenies. The results indicated that bulking of superior full sibs yielded 14.4% more in Local Flint and 11.9% in Metro. However, when bulking was done on their respective open· pollinated progenies, they yielded 35.9% less in Local Flint and 11.8% in Metro. Selection for yield has shown some corresponding improvement in yield components but did not have a significant effect on plant and ear heights nor on the tasselling date